2022
DOI: 10.1186/s12913-022-08032-z
|View full text |Cite
|
Sign up to set email alerts
|

Incentivizing performance in health care: a rapid review, typology and qualitative study of unintended consequences

Abstract: Background Health systems are increasingly implementing policy-driven programs to incentivize performance using contracts, scorecards, rankings, rewards, and penalties. Studies of these “Performance Management” (PM) programs have identified unintended negative consequences. However, no single comprehensive typology of the negative and positive unintended consequences of PM in healthcare exists and most studies of unintended consequences were conducted in England or the United States. The aims o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…A recently published review suggested inappropriate or sub-optimal care, reduction in patient-centred care and exacerbation of inequalities are some of the possible unintended negative consequences of threshold targets for patients. 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently published review suggested inappropriate or sub-optimal care, reduction in patient-centred care and exacerbation of inequalities are some of the possible unintended negative consequences of threshold targets for patients. 17 …”
Section: Discussionmentioning
confidence: 99%
“…A recently published review suggested inappropriate or sub-optimal care, reduction in patient-centred care and exacerbation of inequalities are some of the possible unintended negative consequences of threshold targets for patients. 17 The second behaviour refers to how hospital trusts report the data used for measuring performance in relation to the target. A hospital trust may be encouraged to be more accurate in reporting its data or it could lead to a hospital trust manipulating its data to meet the target.…”
Section: Causes Of Threshold Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial incentives have been observed to increase rates of diagnosis but can also have unintended effects. 17 , 18 The authors are aware of no other research investigating the effect of incentives or their withdrawal on diagnosis. Previous research has observed withdrawal of incentives leads to reduction in documented quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, given that compensation is tied to performance on measures of quality of care, algorithms are often designed to target the quality measures themselves (e.g. reducing 30-day readmissions) as opposed to the underlying goal of improving patient outcomes (Cox et al, 2022; Li and Evans, 2022). Furthermore, the pursuit of profit in the U.S. healthcare system has contributed to the entrenchment of systemic barriers restricting patient access to care such as underinsurance, predatory debt collection, and high administrative costs for billing (Bai et al, 2021; Yearby et al, 2022).…”
Section: Bounded Justice As a Conceptual Framework: Algorithmic (Un)f...mentioning
confidence: 99%